(untitled) (LEARNing Landscapes, 2022)
Our article explores the impact of the global health pandemic on our five-year, multi-sited, collaborative ethnographic study titled Global Youth (Digital) Citizen-Artists and their Publics: Performing for Socio-Ecological Justice (2019-2024). We illustrate how our arts-led, youth-driven ethnographic ”methodology-in-motion” responded to a destabilized world by planning, listening, and seeing differently across local and global research contexts through virtual fieldwork. By focusing on reciprocity and the relational, we examine how researchers, youth participants, and global collaborators, managed to ”lose” and ”find” each other through creative, artistic encounters.